Immunization against pertussis in adolescents and adults. (1st December 2016) - Esposito, S.; Principi, N.; ,
Abstract: Pertussis is a highly contagious infectious disease caused by Bordetella pertussis that can be extremely serious, particularly in young infants. For many years the efforts of health authorities throughout the world to prevent pertussis had the main goals of reducing the morbidity of infants and children under 5 years of age, maintaining protection for several years during the school-age period and developing a significant herd immunity to directly and indirectly reduce the risk of the spread of the disease among young infants and the risk of transmission of the infection from preschool children to infants. However, the increased risk of B. pertussis infection among adolescents and adults due to the waning immunity to this bacterium induced by vaccines and natural infection seems to be the main reason for the resurgence of pertussis. We discuss the reasons for the administration of pertussis vaccines to individuals for whom they were previously not recommended, the expected results of the administration of additional pertussis vaccine doses and the differences in the administration of pertussis vaccines in different countries. An analysis of the literature revealed several reports indicating the need for the modification of immunization schedules against pertussis, with booster doses among adolescents and the need for the vaccination of pregnant women. However, to monitor the true epidemiology of pertussis, effective programmes to collect pertussis cases, adequate reporting systems and vaccination coverage monitoring should be urgently implemented.